2018
DOI: 10.1007/s10620-018-4933-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric Oxide Synthase Is a Novel Biomarker for the Interstitial Cells of Cajal in Stress-Induced Diarrhea-Dominant Irritable Bowel Syndrome

Abstract: Our study demonstrates that early-life stress can influence to ICC and modulate bowel activity and that nNOS might be used as a biomarker for ICC stimulation in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Both sex mice seemed to induce IBS-D, but male mice exhibited a more significant difference in bowel motility under NMS ( Figure 3 B). The more pronounced IBS-D in male mice appeared similar to human clinical manifestations and our previous report [ 14 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Both sex mice seemed to induce IBS-D, but male mice exhibited a more significant difference in bowel motility under NMS ( Figure 3 B). The more pronounced IBS-D in male mice appeared similar to human clinical manifestations and our previous report [ 14 ].…”
Section: Resultssupporting
confidence: 90%
“…Recently, NanoLuc luciferase activity measurement through HiBiT has been reported as an endogenous gene expression analyzing method [ 23 ]. We previously reported that the nNOS expresses higher in the interstitial cell of Cajal in the stress-derived IBS mouse model [ 14 ], but other organs’ nNOS expression could not be analyzed. In this experiment, the nNOS was selected as the target gene, and we tried to analyze the increase in nNOS expression in stress-derived IBS after HiBiT KI mouse generation ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations